The Role of BMI and Blood Pressure in the Relationship Between Total Cholesterol and Disability in Chinese Centenarians: A Cross-Sectional Study - Wang, Shengshu; Jia, Wangping; Yang, Shanshan; Han, Ke; Cao, Wenzhe; Ren, Xueling; Li, Jing; Tai, Penggang; Kou, Fuyin; Liu, Miao; He, Yao (Frontiers in Medicine, 2021)
Background: Lower serum lipid metabolism might be associated with the decline of activity of daily living in extreme longevity group. However, the studies on models and possible paths of this correlation between total cholesterol (TC) and disability in centenarians were scarce. The aim of this study was to verify this correlation, and explore the mediating effect of BMI and blood pressure on this relationship in Hainan centenarians. Methods: We conducted a cross-sectional analysis of 1002 centenarians from China Hainan Centenarians Cohort Study (CHCCS). Data on demographics, anthropometry data, lifestyle and TC level were collected through interviews, physical examinations, and laboratory tests. The Barthel index and Lawton index, measuring the disability status, were used to estimate activity of daily living (ADL) and instrumental activity of daily living (IADL). Multivariable logistic regression model was used to explore the correlation between disability and TC levels. Mediation analyses was used to explore the both direct and indirect effects of TC level on disability. Results: After adjusting for covariates, with 1 mmol/L increment in TC, the adjusted odds ratios (ORs) of ADL severe disability and ADL moderate & severe disability were 0.789(95%CI: 0.650-0.959) and 0.822(95%CI: 0. 0.699-0.966), respectively. There was a significant declining trend of prevalence of different types of disability with increment in TC. The correlation was more pronounced among Hainan female centenarians. In the analysis of mediating effect among female population, BMI significantly mediated the effect of TC levels on different types of disability. BMI and SBP, as chain mediators, multiply and chain mediated the effect of TC levels on IADL. Conclusion: Low TC levels might be correlated with higher frequency of disability in female centenarians, and this correlation might be mediated by BMI and blood pressure.